Regulasi Emosi Mahasiswa Penyandang Disabilitas Tunarungu dalam Relasi dengan Kawan Sebaya - Riahta, Rafidah; Hasanah, Nur; Pratiwi, Ari (Indonesian Journal of Disability Studies, 2015)
Education at the college level provides an opportunity for deaf students to build relationships with students from non-deaf. However, the development of deaf students in inclusive schools sometimes have problems in building relationships that lead to negative emotions of students with hearing impairment. Emotion regulation helps deaf students to manage a negative or positive emotions with environmental conditions in order to maintain relationships with peers. The purpose of this study was to determine how emotion regulation deaf students in relation to peers. This research was conducted by qualitative method of phenomenology. In this study, data collection was done by interview and observation. Subjects of this study were 3 other deaf students with subject selection purposive sampling method. Results of this research is carried emotion regulation deaf students when establishing peer relationships appropriate or not in accordance with the criteria peers who pleases.